Penerapan Model Auditory Intelectually Repetition untuk Meningkatkan Pemahaman Matematis Berbantuan Media Roda Pintar Matematika - Soviana Aprilia; Henry Suryo Bintoro; Jayanti Putri Purwaningrum (Universitas Muria Kudus, 2020)
The purpose of this study is to improve the ability of mathematical understanding, learning activities and teaching skills of teachers through the Auditory Intellectualy Repetition model with assisted by the mathematical smart wheel media. This research is a classroom action research conducted in class IV SDN Sukobubuk 01 Margorejo District Pati Regency second semester 2019/2020 academic year. The research method uses classroom action research consisting of 2 cycles each cycle consisting of 4 stages namely planning, implementing, observing and reflecting. The instruments used in this study were tests of mathematical understanding abilities, observation sheets of student learning activities and teacher teaching skills. Data will be analize test used in this research is quantitative and qualitative data analysis. The results showed, among others: (1) The ability of mathematical understanding through the Auditory Intellectualy Repetition Model assisted by the mathematical smart wheel media increased by 30.29 from the initial condition of 43.35 to 73.64 in the final condition; (2) Student learning activities through the Auditory Intellectualy Repetition Model assisted by mathematical smart wheel media have increased by 23.13 from the initial conditions of 53.12 to 76.25 in the final conditions; (3) Teachers' teaching skills in applying the Auditory Intellectualy Repetition Model assisted by the mathematical smart wheel media increased by 23.5 from the initial conditions of 52.5 to 76 in the final condition